2013
DOI: 10.2147/copd.s39403
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and performance status as prognostic markers in acute hypercapnic respiratory failure due to chronic obstructive pulmonary disease

Abstract: BackgroundIn patients with acute hypercapnic respiratory failure (AHRF) during exacerbations of COPD, mortality can be high despite noninvasive ventilation (NIV). For some, AHRF is terminal and NIV is inappropriate. However there is no definitive method of identifying patients who are unlikely to survive. The aim of this study was to identify factors associated with inpatient mortality from AHRF with respiratory acidosis due to COPD.MethodsCOPD patients presenting with AHRF and who were treated with NIV were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
3
21
1
1
Order By: Relevance
“…In addition to the NEWS, the level of hemoglobin was also found in the present study to be an independent predictor of PIRF‐14. Actually, anemia is associated with the risk of respiratory failure in patients with chronic obstructive pulmonary disease, increased mortality in general ICU patients and increased length of stay in older hospitalized patients . Although the underlying mechanism remains unknown, the present finding might be supported by these reports that anemia is correlated with the risk of PIRF in critical older patients with ICUmv‐lib.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to the NEWS, the level of hemoglobin was also found in the present study to be an independent predictor of PIRF‐14. Actually, anemia is associated with the risk of respiratory failure in patients with chronic obstructive pulmonary disease, increased mortality in general ICU patients and increased length of stay in older hospitalized patients . Although the underlying mechanism remains unknown, the present finding might be supported by these reports that anemia is correlated with the risk of PIRF in critical older patients with ICUmv‐lib.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, a higher prevalence than ours was found in Silverberg et al31 Possible explanations are a different case mix where, for example, diabetes was twice as frequent as in our population and the exclusion from our study of patients admitted previously for AECOPD. In a study of patients treated with noninvasive ventilation for AECOPD, Mydin et al18 found higher prevalence of anemia than in our population. Probably, the inclusion of only patients in need of noninvasive ventilation shifted the case mix with regard to severity of illness compared to our population, which might explain the in-hospital mortality rate of 33% compared to only 7% in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Iron deficiency anemia in ventilated COPD patients, and in those with chronic respiratory failure, is known to increase work of breathing and minute ventilation, (30) (31) (32) and transfusion may help to wean these patients from mechanical ventilation (33) (34). There is also a correlation between pulmonary function (Forced expiratory volume, FEV 1 ) and iron status, exacerbated by inflammation and nutritional deficiencies, which many critically ill patients have (35).…”
Section: Discussionmentioning
confidence: 99%